2017
DOI: 10.4103/ijem.ijem_72_17
|View full text |Cite
|
Sign up to set email alerts
|

The serological and biochemical markers of adrenal cortex and endocrine pancreas dysfunction in patients with Hashimoto's thyroiditis: A hospital-based pilot study

Abstract: Background:The prevalence of both islet cell and adrenal autoimmunity among Asian Indian hypothyroidism patients with Hashimoto's thyroiditis (HT) is lacking in literature.Objectives:The objective of this study was to assess the proportion of Addison's disease (AD) and type 1 diabetes mellitus (T1DM) in patients with HT.Materials and Methods:The patients with hypothyroidism due to HT were included in this study over 2 years. Primary hypothyroidism was defined as high serum thyroid-stimulating hormone (>5.5 mIU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In patients with autoimmune thyroid disease, the presence of GAD Ab was shown to be consistent with the onset of diabetes, lower body mass index, higher hemoglobin A1c level, and higher frequency of insulin therapy at a younger age. However, a recent survey [ 70 ] showed that less than twenty percentage of Asian Indian female patients suffering from hypothyroidism presented islet cell Ab with normal GAD Ab. Prevalence of islet antibody in patients with autoimmune thyroid was also low.…”
Section: Roles Of Thyroid and Thyroid Hormone In Pancreas Pathogenmentioning
confidence: 99%
“…In patients with autoimmune thyroid disease, the presence of GAD Ab was shown to be consistent with the onset of diabetes, lower body mass index, higher hemoglobin A1c level, and higher frequency of insulin therapy at a younger age. However, a recent survey [ 70 ] showed that less than twenty percentage of Asian Indian female patients suffering from hypothyroidism presented islet cell Ab with normal GAD Ab. Prevalence of islet antibody in patients with autoimmune thyroid was also low.…”
Section: Roles Of Thyroid and Thyroid Hormone In Pancreas Pathogenmentioning
confidence: 99%